EFFECTIVENESS COMPARISON OF CAMBODIAN LEAF EXTRACT (Plumeria acuminata Ait) WITH JATROPHA LEAF EXTRACT (Jatropha curcas L) IN HEALING OF MINOR RECURRENT APHTOSA STOMATITIS (RAS) : Perbandingan Efektifitas Ekstrak Daun Kamboja (Plumeria Acuminata Ait) Dengan Ekstrak Daun Jarak Jauh (Jatropha Curcas L) Terhadap Penyembuhan Minor Recurrent Aphtosa Stomatitis (Ras) - IGN Putra Dermawan; Intan Kemala Dewi; I Nyoman Gede Juwita Putra (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2021)
Introduction: Recurrent aphthous stomatitis (RAS), also known as canker sores, is an inflammation that occurs in the oral mucosa. Frangipani leaf extract and jatropha leaf extract are known to contain saponins, tannins and flavonoids that function as wound healers and antimicrobials. Purpose: Determine whether the administration of frangipani leaf extract (Plumeria acuminata Ait) is more effective in curing recurrent aphthous stomatitis than jatropha leaf extract (Jatropha curcas L). Materials and Methods: The method used is experimental study with a purposive sampling of 30 people. frangipani leaf extract (Plumeria acuminata Ait) and jatropha leaf extract (Jatropha curcas L) were applied to each of 15 samples. Statistical calculations using the Independent T-test. Result and Discussion: The results showed that the mean difference in diameter reduction of recurrent aphthous stomatitis in the first sample group of frangipani leaf extract (Plumeria Acuminata Ait) was 1.13 mm, while in the second sample group Jatropha leaf extract (Jatropha curcas L) was 0.47 mm. From the results of the Independent T-Test test on frangipani leaf extract (Plumeria acuminata Ait) obtained a sig value of 0.002 (p<0.05) and jatropha leaf extract (Jatropha curcas L) of 0.002 (p<0.05), indicating that there is the difference between the use of frangipani leaf extract (Plumeria acuminata Ait) and jatropha leaf extract (Jatropha curcas L) in the treatment of recurrent aphthous stomatitis. Conclusion: frangipani leaf extract (Plumeria acuminata Ait) was more effective in curing recurrent aphthous stomatitis (SAR) than jatropha leaf extract (Jatropha curcas L).